The study skills toolkit for students with dyslexia - Gribben, Monica (Los Angeles, [Calif.] ; London : SAGE, 2012)
This title provides ideas and advice to help dyslexic students with their studies. Packed with helpful advice, hints, checklists and templates, this book will help you improve your study skills throughout your time at university.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Study skills; Dyslexics -- Education (Higher)